The importance of supervised internship and planning for geography teacher training: experience report (Research, Society and Development, 2020)
This article discusses the importance of the supervised internship, an activity that is required in the different courses, mainly in the degree courses, particularly this work aims to emphasize the importance of the internship and planning for the full degree course in geography. The practice of supervised internship in undergraduate programs develops in students not only an understanding of the theories studied during graduation, but also its applicability and reflection on the practice that starts from the moment the student enters the classroom as an intern, in this At the moment, the intern has to be able to develop the role of teacher. For this, planning is necessary, so that he can contribute to the teaching-learning of children. To support the discussion, the investigative methodology was used, as well as the qualitative where it seeks to investigate and qualify the supervised internship and planning for teacher training. Thus, to validate the results obtained, the classes of the 6th year “A” and the 3rd year “A” were characterized by the municipal school Nila Ferreira da Silva, in the city of Fagundes, Paraíba. It was observed the learning difficulties that these two classes presented even with the teaching systems that the teacher of the class applied. In short, the supervised internship will bring the truth of the pleasures and challenges that the future teacher will face in his daily life as a teacher, learning to deal with daily difficulties and achieve his greatest goal, which is to promote teaching and learning.